ANALISIS GAYA BAHASA PADA LIRIK LAGU ANAK-ANAK - Ira Eko Retnosari; Rahayu Pujiastuti (Buana Bastra, 2025)
This study aims to describe the language style in children's song lyrics. The focus of this study is children's song lyricsthat contain language styles. The data source for this study is children's songs sung by Tasya. The data for this study is the language stylefound in the song lyrics. The data collection techniqueused in this study is the documentation method. The procedurefor collecting data in this study was (1) downloading the song lyrics, (3) reading the song lyrics, (4) marking them with a highlighter, (5) classifying them, and (6) coding the data.The data analysis technique used in this study is descriptive qualitative. The procedure foranalyzing the research data is (1) analyzing the data, (2)interpreting the data, (3) drawing conclusions. Based on the data analysis, it can be concluded that the stylistic devices in the lyrics ofchildren's songs sung by Tasya include (1)repetition, (2) metaphor, (3) litotes, (4) hyperbole, (5) metonymy, (6)parallelism, and (7) personification. Of the seven styles of language, repetition andpersonification are the most widely used in children's song lyrics. Meanwhile, metonymy and litotes are the least used.